Automated QUAL2Kw for Water Quality Modeling in the Tunggak River, Gebeng, Kuantan, Malaysia - Hossain, Mohamed Amjed; Nasly, Mohamed Ali; Islam, Mir Sujaul (2013)
The Tunggak River in Gebeng, Kuantan receives industrial waste water from Gebeng industrial estate that resulted decrease in DO concentrations and increase in ammoniacal nitrogen as well as other nutrients in the river flow. QUAL2Kw water quality model was calibrated and confirmed using the water quality data of Tunggak River to assess the water quality. With some exceptions the model represented the field data quite well and confirmed that the model is applicable for simulation for the river. The results ascertained that combination of existing wastewater management with QUAL2Kw model might be a unique strategy for resolving the industrial water pollution.